Which factors predict discordance between a patient and physician on a gout flare?. (13th August 2020) - Jagpal, Aprajita; Rahn, Elizabeth J; Mudano, Amy S; Dalbeth, Nicola; Taylor, William; Saag, Kenneth G; Singh, Jasvinder A; Cavagna, Lorenzo; Uhlig, Till; Perez-Ruiz, Fernando; McCarthy, Geraldine; Gerritsen, Martijn; et al.
Abstract: Objective: To investigate the factors associated with discordance between patient and physician on the presence of a gout flare. Methods: Patients' self-reports of current gout flares were assessed with the question, 'Are you having a gout flare today?' which was then compared with a concurrent, blinded, physician's assessment. Based on agreement or disagreement with physicians on the presence of a gout flare, flares were divided into concordant and discordant groups, respectively. Within the discordant group, two subgroups—patient-reported flare but the physician disagreed and physician-reported flare but the patient disagreed—were identified. The factors associated with discordance were analysed with multivariable logistic regression analysis. Results: Of 268 gout flares, 81 (30.2%) flares were discordant, with either patient or physician disagreeing on the presence of a flare. Of the discordant flares, in 57 (70.4%) the patient reported a flare but the physician disagreed. In multivariable logistic regression analysis adjusted for demographics, disagreement among patients and physicians on the presence of a gout flare was associated with lower pain scores at rest [odds ratio (OR) for each point increase on 0–10 point pain scale 0.81 (95% Wald CI 0.73, 0.90), P < 0.0001] and less presence of joint swelling [OR 0.24 (95% CI 0.10, 0.61), P = 0.003] or joint warmth [OR 0.39 (95% CI 0.20, 0.75), P = 0.005]. Conclusion: Although patients and physicians generally agree about the presence of gout flare, discordance may occur in the setting of low pain scores and in the absence of swollen or warm joints.